Liturgy affects the parameters of gas discharge visualization, acupuncture points and neuro-endocrine-immune complex - Igor Popovych; Valeriy Babelyuk; Walery Zukow; Radosław Muszkieta; Galyna Dubkova; Liliya Nesterova; Viktor Hubyts'kyi; Volodymyra Bilas; Vira Musiyenko; Teodor Seniv; Viktor Mis'ko; Roman Babylyuk; et al. (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Background. The impact of religion on the human body has been the subject of a number of studies, including ours. The proposed article is a continuation of them. Purpose of the study: to detect in the supervised observation the characteristic effects of the Liturgy on some biophysical and physiological parameters of healthy people. Materials and methods. Under a observations were 10 healthy men by age 26-56 years. In the morning in basale condicions registered parameters of Gas Discharge Visualization (GDV), electroskin conductivity of Points Acupuncture (CPA), Heart Rate Variability (HRV), Leukocytogram, phagocytic function of neutrophils as well as anxiety and plasma levels of main adaptive hormones: Cortisol, Triiodothyronine and Testosterone. After testing, one volunteer went to a chapel to attend a half-hour Liturgy, and another volunteer was in the park nearby, serving as a control. After that, both participants returned to their duties, and after 1 hour all tests were repeated. Results. The characteristic effects of the Liturgy are: minimization the decrease in CPA TR(X) and G8Dg on the right, reactive anxiety, cortisolemia and one marker of vagal tone; limitation the increase in the area of the GDV in the frontal projection and the intensity of phagocytosis; initiation an increase in plasma testosterone, entropy of the leukocytogram and the proportion of rod-core neutrophils, as well as reversion the decrease in the tone of the vagus and the decrease of the energy of the virtual seventh chakra, which takes place in the control group. Conclusion. Liturgy affects the parameters of gas discharge visualization, acupuncture points and neuro-endocrine-immune complex in healthy men.